The dionisian question, between the tragic philosophy and the will to power - Hinostroza Rivera, Dino Arturo (2024)
In this text, an archeology of Nietzsche’s thought will be made and a thread will be woven between the Dionysian question and the Will to Power, and it will be argued that this is a reformulation of that for which Nietzsche himself had to go through a process of metamorphosis that allowed him to overcome the limitations of language and traditional philosophical systems, debtors of metaphysics and dialectic. The text consists of two parts. In the first part, the author will review the concepts of the Apollonian and the Dionysian in his first work and the poor reception it received from the academy due to what Nietzschehimself called an “ambiguity”. In a second part, certain elements of his late bibliography will be reviewed to show how the Will to Power is inspired by the Dionysian question, a key element of tragic philosophy.